PHP Ajax cookbook : over 60 simple but incredibly effective recipes to Ajaxify PHP Websites - Anbiah, R. Rajesh Jeba (Community experience distilled., 2011)
This book contains a collection of recipes with step-by-step directions to build SEO-friendly websites using standard Ajax tools. Each recipe contains behind-the-scene explanations to PHP Ajax questions. This book is an ideal resource for people who like to add Ajax features to websites and who prefer standards and best practices for building SEO-friendly websites. As the book covers advanced topics, readers need to be aware of basic PHP, JavaScript and XML features.